Cooperation Between Institutions of the European Union and Its Member States in the Creation of Climate Protection Policy - Świat, Piotr; Bukowska, Joanna (Review of European and Comparative Law, 2019)
Climate policy is a complexed area of cooperation between Member States and European Union institutions. The ambitious goals that the EU sets for itself in this matter are not always possible to be met by all Member States, hence the ability to work out compromise solutions is of great importance. Member States have different internal conditions, which determine the objectives of their economic and energy policies, therefore they do not always have convergent interests in this area. The decision-making centre where EU climate protection policy is created is: the European Council, where key elements of this policy are agreed (such as reduction targets), and so-called an ‘institutional triangle’, i.e. EU Council, European Parliament and European Commission which are directly involved into the legislative process. This configurations is a platform where cooperation of the Member States manifests itself in various forms and intensity and where these countries may attempt to force their interests in the process of creating EU policy. The authors present the legal bases of the European Union's competences in the field of climate policy and the role of the EU institutions in its creation with particular focus on mechanisms that allow Member States to influence the shape of that policy.